2007
DOI: 10.2175/106143006x136810
|View full text |Cite
|
Sign up to set email alerts
|

Application of Activated Sludge Model No. 3 for the Modeling of Organic Matter Biodegradation at Thermophilic Temperatures

Abstract: The primary aim of our research was to investigate the applicability of activated sludge models (ASM) for aerobic thermophilic processes, especially autothermal thermophilic aerobic digestion (ATAD). The ASM3 model (Gujer et al., 1999) theoretically seems to be the most suitable, because storage plays an important role in a batch-feed cycle system like ATAD. The ASM3 model was extended with an activation step of the thermophilic organisms. This model was calibrated and verified by independent test results, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Based on simulating data from 13 nitrifying-denitrifying facilities, Choubert et al (2007) proposed the following modifications to the default ASM1 parameter values: max,A = 0.45 d -1 at 10°C; b A = 0.17 and 0.13 d -1 at 20 and 10°C, respectively; and anoxic Y H = 0.54 gCOD/gCOD at 10°C. Kovacs et al (2007) extended ASM3 using an activation step for the thermophilic organisms for modeling autothermal thermophilic digestion, which was uncoupled to the rest of ASM3, and calibrated and verified the new model with different sets of data. Hwang and Oleszkiewicz (2007) reported that the sudden temperature decrease from 20 to 10 °C caused a 20% greater decrease of the nitrification rate than predicted by using the temperature correction factor of 1.072.…”
mentioning
confidence: 99%
“…Based on simulating data from 13 nitrifying-denitrifying facilities, Choubert et al (2007) proposed the following modifications to the default ASM1 parameter values: max,A = 0.45 d -1 at 10°C; b A = 0.17 and 0.13 d -1 at 20 and 10°C, respectively; and anoxic Y H = 0.54 gCOD/gCOD at 10°C. Kovacs et al (2007) extended ASM3 using an activation step for the thermophilic organisms for modeling autothermal thermophilic digestion, which was uncoupled to the rest of ASM3, and calibrated and verified the new model with different sets of data. Hwang and Oleszkiewicz (2007) reported that the sudden temperature decrease from 20 to 10 °C caused a 20% greater decrease of the nitrification rate than predicted by using the temperature correction factor of 1.072.…”
mentioning
confidence: 99%